Analyse de l’activité à bord de dragues aspiratrices : une méthodologie exploratoire combinant données psychologiques et physiologiques - Bastien Sennegon; Benoit Grison; Philippe Ravier; Olivier Buttelli (Activités)
The purpose of this study is to explore a methodology combining two types of data, psychological and physiological, through an ergonomic analysis of the activity. Two field studies were conducted: the stationary suction dredger situation, and the moving suction dredger situation, where we focused on the bridge assistant, responsible for the dredging activity. Two orders of data are considered: psychological and physiological. From a psychological point of view, our methodology cross-referenced ethnographic observations with non-directive interviews. At the physiological level, heart-rate measurements (R-R interval) were continuously recorded, throughout the activity. Our results proceed from the confrontation of these “objective” and “subjective” data sources. The workload at this work station appears to be considerable, with many short actions. It would seem necessary to maintain a high level of vigilance, due to the various parameters to be taken into account, and to the multiple adjustments which must be made during the task time. The activity can become more complex, depending on the nature of the seabeds: many variations can take place, and there may be occurrences of stress when dredging chaotic seabeds. This “integrated” approach to human activity should lead to improved safety for the sailors.